2019
DOI: 10.1021/acsami.9b01359
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Energy Density by Tailoring the Interface in Hierarchically Structured TiO2–BaTiO3–TiO2 Nanofillers in PVDF-Based Thin-Film Polymer Nanocomposites

Abstract: Dielectric polymer nanocomposites with a high breakdown field and high dielectric constant have drawn significant attention in modern electrical and electronic industries due to their potential applications in dielectric and energy storage systems. The interfaces of the nanomaterials play a significant role in improving the dielectric performance of polymer nanocomposites. In this work, polydopamine (dopa)-functionalized TiO2–BaTiO3–TiO2 (TiO2–BT–TiO2@dopa) core@double-shell nanoparticles have been developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 84 publications
1
61
0
Order By: Relevance
“…Table 2 summarizes the energy storage performance of TiO 2 @SrTiO 3 @PDA NWs/PVDF NC and some previously reported dielectric NCs. It can be observed that the NCs in this study exhibit comparable or higher discharge energy density than that of previously reported dielectric NC films 16,[47][48][49][50][51][52][53][54][55][56][57] . High discharge energy density is due to the additional interfacial polarization induced in the interfacial region of TiO 2 @SrTiO 3 NWs and high permittivity and low remnant polarization of paraelectric ceramic SrTiO 3 shell.…”
Section: Dielectric Properties Of the Tio 2 @Srtio 3 @Pda Nws/pvdf Nasupporting
confidence: 56%
“…Table 2 summarizes the energy storage performance of TiO 2 @SrTiO 3 @PDA NWs/PVDF NC and some previously reported dielectric NCs. It can be observed that the NCs in this study exhibit comparable or higher discharge energy density than that of previously reported dielectric NC films 16,[47][48][49][50][51][52][53][54][55][56][57] . High discharge energy density is due to the additional interfacial polarization induced in the interfacial region of TiO 2 @SrTiO 3 NWs and high permittivity and low remnant polarization of paraelectric ceramic SrTiO 3 shell.…”
Section: Dielectric Properties Of the Tio 2 @Srtio 3 @Pda Nws/pvdf Nasupporting
confidence: 56%
“…However, the dielectric loss is higher than in the neat polymer matrix, and the dielectric strength of the neat polymer reference is quite low. [ 189,190 ]…”
Section: Endeavors To Enhance Dielectric Strengthmentioning
confidence: 99%
“…The sharp peaks at 1435 and in the range of 400-850 cm À1 represent Ti-O stretching. 6,26,27 The small doublet peaks at 2923 and 2854 cm À1 are assigned to asymmetric and symmetric -CH 2 vibrations, respectively. 28 This confirms the successful synthesis of BT NFs to be used as nanofillers in capacitor devices.…”
Section: Resultsmentioning
confidence: 99%
“…An ideal dielectric should exhibit a high dielectric constant (e r ) or polarization (P) as well as high breakdown strength (E b ) for high energy density (U d ), as given by eqn (1), 6 U…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation